PENGEMBANGAN MEDIA INTERAKTIF BERBASIS KEARIFAN LOKAL SEBAGAI MATERI MENYIMAK CERITA RAKYAT - Wiranty, Wiendi; Melia, Melia (Universitas Sebelas Maret, 2020)
The research was conducted to develop interactive learning media based on local wisdom and its impact on improving student learning outcomes in listening to folk tales. The results of this study are expected to produce products in the form of learning media that are in accordance with the characteristics of the material and students and improve student learning outcomes. This research method is the Research and Development method with a development design using the hannafin and peck design. In accordance with the research objectives that have been stated, the data sources used in this study were obtained from the media feasibility validation questionnaire, student learning outcomes tests before and after the use of the media. The research subjects in this study were students of class XI SMAN 1 Segedong. As for the independent variable in this study is interactive media based on local wisdom, while learning outcomes as the dependent variable in this study. The data collection techniques used in this research are indirect communication techniques and measurement techniques. The instruments used in data collection were a validation validation questionnaire and a test of student learning outcomes with multiple choice questions. The results showed that the average student learning outcomes from the initial test increased by 68.16 to 80.31 in the final test. Then based on testing using the effect size, the value was 0.86 with large criteria. It can be concluded that interactive media based on local wisdom has a major effect on improving student learning outcomes.